On the equivalence of problem-oriented databases - Lebiediewa, Swietlana (Zielona Góra: Uniwersytet Zielonogórski)
A comparison is made between problem-oriented databases for multistage decision making and general-purpose databases. An exemplary problem-oriented database IDEN for supporting the process of multistage identification is discussed in detail. An equivalence condition for problem-oriented databases is formulated and then the equivalence with respect to data structures and operations is proved for hierarchical, network and relational models of the IDEN database.
Keywords: problem-oriented database; data manipulations language; distributed databases; equivalence of databases